Not all cemented hips are the same: a register-based (NJR) comparison of taper-slip and composite beam femoral stems. (4th May 2019) - Kazi, Hussain A; Whitehouse, Sarah L; Howell, Jonathan R; Timperley, A John
Abstract : Background and purpose — No difference in outcome has been demonstrated comparing cemented taper-slip and composite beam designs in short-term randomised trials; we assessed outcome differences using a registry analysis. Patients and methods — All cemented stems with > 100 implantations were identified in the National Joint Registry of England and Wales from April 1, 2003 to September 31, 2013 and categorised as taper-slip or composite beam. Survival analyses using Kaplan–Meier and Cox regression were performed. Results — We identified 292, 987 cemented arthroplasties, of which 16% (47, 586) were composite beam stems, with taper-slip stems making up the remainder (n = 245, 401). There was a statistically significant increased chance of revision in the composite beam group compared with the taper-slip group (1.7% vs 1.3%, p < 0.001) but statistically no significant differences of survival estimates (p = 0.06). When the 2 groups were segregated to delineate the most implanted model in each category, the differences became more profound with the most implanted taper-slip stem (Exeter V40) showing statistically and clinically significant superior 8-year survival: 97.9% compared with 97.6% for all other taper-slip; 97.5% for the most implanted composite beam (Charnley cemented stem); and 97.7% for all other composite beam. Interpretation — There was an increased incidence of revision for composite beam stems. The most implanted taper-slip stem demonstrated significant survival advantage vs. all other stems.